Exploring the Role of Microlearning in Lifelong Learning: A Bibliometric Review - Judijanto, Loso (The Eastasouth Journal of Learning and Educations, 2025)
This study explores the role of microlearning in supporting lifelong learning through a bibliometric review of existing literature. Microlearning, characterized by brief, focused learning sessions, has gained prominence as an effective strategy for delivering flexible and accessible educational content. The study highlights the alignment between microlearning and lifelong learning, emphasizing its potential for self-directed and informal learning in both personal and professional contexts. By analyzing key trends, authors, and emerging research areas, this review identifies the growing integration of microlearning with digital learning tools, mobile applications, and emerging technologies such as artificial intelligence and virtual reality. The findings also reveal challenges in microlearning, such as balancing brevity with depth, managing content fragmentation, and overcoming technological barriers to access and personalization. Future research directions include examining microlearning's impact on long-term retention, its pedagogical implications, and its integration into formal education systems. This study contributes to a deeper understanding of microlearning’s role in lifelong learning and provides insights into its future development and applications in diverse educational settings.